Critique of Digitality - Distelmeyer, Jan. (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Palgrave Macmillan, 2022)
Dealing with digitality is one of the most urgent challenges of the present. The increasing importance and spread of computer technology not only challenges societies and individuals - this development also puts pressure on the concept of digitality, which tries to grasp the totality and peculiarity of the conditions and consequences of electronic digital computing (in all its forms). However, precisely because digitality is commonplace, so should be its critique, its analysis and assessment.How can an analysis do justice to both fundamental characteristics and changing concrete forms, infrastructures, and practices? How do the developments of a digitalization that programmatically encompasses forms of networking, embedding, and autonomization shape media, cultures, and societies? How do "artificial intelligence" and "algorithmic government" relate to each other, how does the immateriality of "the digital" fit with the materiality of computers? How does the changing status and scope of this technology mediate itself? This volume introduces ongoing debates and develops its own approach to the critique of digitality, asking about forms of interfaces and processes of governance. The author Prof. Dr. Jan Distelmeyer teaches media history and theory in the cooperative program European Media Studies at the University of Applied Sciences Potsdam and the University of Potsdam. The translation was done with the help of artificial intelligence (machine translation by the service DeepL.com).A subsequent human revision was done primarily in terms of content, so that the book will read stylistically differently from a conventional translation.
Digitality and Criticism -- Interface and Conduct -- Program and Everyday Life.
Keywords: Digital media; Popular Culture; Mass media; Motion pictures; Digital and New Media; Popular Culture; Media Sociology; Audio-Visual Culture